Human Errors Determinants among Indonesian Oil and Gas Workers: Sleep, Distress, Recovery - Achmad Dahlan; Fatma Lestari; Baiduri Widanarko (Universitas Airlangga, 2026)
Introduction: Human error is a major safety concern in upstream oil & gas operations because small performance failures may lead to near-misses, incidents, illness, and production loss. This study examined the determinants of human error among Indonesian upstream oil and gas workers, with emphasis on sleep, psychosocial strain, psychosocial strain, physical activity, work characteristics and recovery outside work. Method: A cross-sectional online survey was conducted among oil and gas workers in Indonesia. Of 1,650 respondents, 1573 valid responses were included in the analysis. Human errors was assessed using a composite score based on self reported errors and near-misses. Independent variables include age, sleep duration, sleep quality, physical activity, work entity, rotation type, shift type, distress, and secondary employment. Binary logistic regression was used to identify determinant factors associated with high human error. Result: High human errors was significantly associated with poor sleep quality (OR 5.08), high distress (OR 5.71), moderate distress (OR 2.83), maintenance and production work (OR 2.05), off-duty secondary employment (OR 1.69), short sleep durations of les than 7 hours (OR 1.55), and low physical activity (OR.155). Workers age 50-54 years had lower odds of high human error (OR 0.39). Rotational type, shift type, and on-duty secondary employment were not significant. Conclusion: Human error in this population appears to be driven more by sleep problems, psychosocial strain, inadequate recovery, and operational job demands. Prevention strategies should therefore extend beyond roster design and include sleep health, psychosocial risk control and recovery protection program and policy.